2001
DOI: 10.1542/peds.107.5.e70
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents With Cystic Fibrosis: Family Reports of Adolescent Health-Related Quality of Life and Forced Expiratory Volume in One Second

Abstract: ABSTRACT. Purpose. To assess the relationship between adolescent and parent reports of adolescent health-related quality of life (HRQL) and between adolescent pulmonary function (forced expiratory volume in 1 second as percent of predicted) and reporter perceptions of adolescent health.Methods. Twenty-four adolescents with cystic fibrosis (CF), their mothers, and their fathers completed the Child Health Questionnaire during routine CF clinic visits at 2 urban hospitals. Patients were between the ages of 11 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
1
19
1
6
Order By: Relevance
“…(26) However, in individuals under 18 years of age, no such correlation was observed. (28) In three studies conducted in the 2000s, (12,13,29) the correlation between QoL and FEV 1 in individuals with CF was assessed by the Child Health Questionnaire, with conflicting results. In two of the studies, (12,13) no such correlation was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(26) However, in individuals under 18 years of age, no such correlation was observed. (28) In three studies conducted in the 2000s, (12,13,29) the correlation between QoL and FEV 1 in individuals with CF was assessed by the Child Health Questionnaire, with conflicting results. In two of the studies, (12,13) no such correlation was found.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors of the third study observed that adolescents and adults with abnormal FEV 1 reported a poor perception of their physical health. (29) In a recent study involving the use of the CFQ, adults with CF and with altered FEV 1 were found to have lower scores in the domains related to physical functioning and health, indicating that anxiety, depression, and pulmonary function correlate with self-reported QoL. (4,21) Most studies suggest that self-perceived health is directly related to age and to respiratory system impairment, becoming more evident in adolescents and adults with greater lung injury, (4,21,26) as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Powers et al, 237 from Massachusetts, set out to administer the CHQ to 39 adolescent patients, their mothers and fathers. The response rates were 82% for patients and mothers but only 64% for fathers.…”
Section: Medline = 1064 Retrieved Embase = 1281 Retrievedmentioning
confidence: 99%
“…Both a child (CHQ-CF 87) and caregiver version (CHQ-PF 50) of the CHQ are available and have been tested in normative populations as well as children with a wide variety of chronic diseases (13,17,25,26). CHQ-CF 87 and CHQ-PF 50 scales include physical functioning, role/social limitations due to physical health, bodily pain, general health, role limitations due to emotional/behavior problems, behavior, mental health and self-esteem.…”
Section: Instrumentmentioning
confidence: 99%
“…The adolescent's unique position in the transition zone between childhood and adulthood renders such reports from either parent or child even more susceptible to potential misinterpretation. Studies of adolescent patients with a broad range of chronic illnesses indicate that parents may report a greater impact of illness on the functioning of their children than the children themselves (13)(14)(15)(16)(17)(18). Similar patterns in the reporting of HRQOL may also be present in adolescent solid organ transplant recipients.…”
mentioning
confidence: 97%